Current Applications of Bacteriocin - Abebe Worku Negash; Berhanu Andualem Tsehai (International Journal of Microbiology)
Bacteriocins are multifunctional, ribosomally produced, proteinaceous substances with pronounced antimicrobial activity at certain concentrations. They are produced by bacteria and certain members of archaea to inhibit the growth of similar or closely related bacterial strains. These molecules have antimicrobial activity against pathogenic and deteriorating bacteria, which justifies their biotechnological potential. They are classified into 3 major classes based on their structural and physicochemical properties: class I bacteriocin, class II bacteriocin, and class III bacteriocin. Bacteriocins inhibit the growth of target organisms by functioning primarily on the cell envelope and by affecting gene expression and protein production within cells. The use of bacteriocins has been reported for the following: food preservation, diverse therapeutic purposes such as treatment of peptic ulcer, spermicidal agent, and woman care, anticancerous agent, veterinary use, skincare, and oral care, and also for plant growth promotion in agriculture among others.